THE ROLE OF OCCUPATIONAL SAFETY AND SAFETY IN HEAT SUPPLY SYSTEM BUILDINGS (BOILERS) - Davurov B. A (European Journal of Life Safety and Stability (2660-9630), 2021)
The article contains analysis and recommendations on reducing man-made hazards in the construction of heat supply systems, which are an important sector of the economy, as well as compliance with the requirements of labor protection and safety of workers working in such facilities.